CAVE SETTLEMENT POTENTIAL OF CAVES AND ROCK SHELTERS IN ACEH BESAR REGENCY: POTENSI HUNIAN GUA DAN CERUK DI KABUPATEN ACEH BESAR - Taufiqurrahman Setiawan (BRIN, 2020)
Abstract The evidence of prehistoric life in Aceh has been proven by the results of archeological research conducted by the North Sumatra Archaeological Institute. Until now, the research only focuses on the eastern coast and the central mountains of Aceh. The western coast of Aceh, which also has the potential to provide information, has never been studied. The western coast of Aceh is an area that has a wide karst landscape with many caves that might be used as a settlement in the past. One method used to predict such caves included a topographic map, a geological map, and a digital elevation model (DEM). The inventory results of caves on the western coast of Aceh were also used as preliminary data to obtain the distribution of caves and rock shelters. In this study, the area surveyed was Aceh Besar Regency. Three parameters of inhabited caves, i.e. morphology and genesis, environment, and archaeological content, were used to describe the potential of each cave. Of eleven caves and rock shelters, three caves are qualified as the past settlement and potential for further research, four caves are qualified as the past settlement but not potential for further research, and four caves are neither qualified as a settlement nor potential for further research. Abstrak Bukti adanya kehidupan masa prasejarah di Aceh telah dibuktikan dengan hasil penelitian arkeologi yang dilakukan oleh Balai Arkeologi Sumatera Utara. Sampai saat ini penelitian masih terfokus di pesisir timur dan pegunungan tengah Aceh, Pesisir barat Aceh belum pernah diteliti. Pesisir barat Aceh merupakan wilayah yang memiliki bentangalam kars cukup luas, dan memiliki potensi gua yang mungkin digunakan sebagai lokasi hunian pada masa lalu. Salah satu metode yang digunakan adalah memprediksi keberadaan gua dengan peta topografi, peta geologi, serta digital elevation model (DEM). Selain itu, hasil inventarisasi gua yang pernah dilakukan di wilayah pesisir barat Aceh juga digunakan sebagai data awal untuk memperoleh sebaran gua dan ceruk. Pada penelitian ini lingkup wilayah yang disurvei adalah Kabupaten Aceh Besar. Tiga parameter gua hunian, yaitu morfologi dan genesa, lingkungan, serta kandungan arkeologis, digunakan untuk memperoleh gambaran potensi masing-masing gua. Sebelas gua dan ceruk yang telah ditemukan menunjukkan adanya tiga buah gua berpotensi sebagai lokasi hunian dan diteliti lebih lanjut, empat gua berpotensi sebagai lokasi hunian tetapi tidak berpotensi untuk diteliti, dan empat gua berkategori tidak potensial sebagai lokasi hunian.